THE ROLE OF PULMONARY REHABILITATION IN ACUTE EXACERBATIONS OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE - RAHMAD; NARASATI, SHABRINA; NUGROHO, EKO; WITJAKSONO, DJOKO; LESTARI, DWI INDRIANI; NUGROHO, M. BARLIAN; RACHMAWATI, SAMIAH; RIDWAN, M. (International Journal of Applied Pharmaceutics, 2020)
Objective: Chronic obstructive pulmonary disease (COPD) reduces lung function and generates systemic effects that decrease the quality of life. COPD is a major cause of chronic morbidity and mortality worldwide. Pulmonary rehabilitation can reduce symptoms of dyspnea and improve exercise capacity and quality of life in COPD patients. Methods: We report a case of a 60 y old male with an acute exacerbation (AE) of COPD and pneumonia. The inpatient pulmonary rehabilitation program was 5 consecutive days of 3 repetitions of cough control, 2 sets of 6 repetitions of pursed-lip breathing, 2 sets of 6 repetitions of deep breathing exercises, postural drainage, and manual clapping twice daily. Postural drainage in the lateral basal segment and manual clapping in the right lower lobe was chosen according to the chest x-ray (CXR). Results: At the initial visit, the following information was noted: inspiration capacity with incentive spirometry, 600 cc/s; chest expansion, 1.5 cm; and single-breath counting (SBC), 11. The activities of daily living (ADL) score according to the Barthel Index was 70, and CXR results showed COPD and pneumonia in the right lower lobe. After 5 d of pulmonary rehabilitation, there was a clear airway and improvement in shortness of breath (SOB), and the following was noted: incentive spirometry, 900 cc/s; chest expansion, 2 cm; SBC, 20; and Barthel Index score, 100. Conclusion: Early inpatient pulmonary rehabilitation in COPD AEs is clinically effective and safe, controls breathing and coughing, strengthens the respiratory muscles, and improves the clearing of the airway, which improves the patient’s pulmonary function capacity and quality of life.